INTEGRASI POLITIK HUKUM TERHADAP TINDAK PIDANA PEMBERITAAN PALSU (HOAX) DI INDONESIA - Khoiruddin Manahan Siregar (IAIN Padangsidimpuan, 2018)
The spread of false news (hoax) is currently widespread in various media. Both print and online media, starting from the spread of someone through broadcast messages, print media, online media, and other mass media. Sadly, most of the people easily believe in the existence of false news (hoax) without finding out the real truth. Hoax news is fake news that is being falsified or reversed from the real reality. This research was conducted to find out how the response and actions of the government in the spread of hoax and criminal acts should be appropriate for disseminating hoax through their legal politics. This research is expected that the general public users of social media, especially among academics, can be more systematic in processing information and sorting out reliable information